RELEVANSI TEORI KEADILAN JOHN RAWLS UNTUK PEMBERDAYAAN MASYARAKAT - Tb. Soleh Ahmad; Maisya Aqilah (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2023)
In the community development process, understanding and integrating procedural justice is expected to be the key to success. In the process of community development there must be a procedure in which all elements of society actively participate in determining the rules of the game, strategies and working mechanisms of a program. In Indonesia, Community Development includes and has become a separate discussion in addressing issues of poverty, justice and human rights, law, ecological crises and other social issues which are the scope of community development. With Rawls's theoretical framework, this article concludes that justice can also be called a tool to unite people.